Developing a water strategy for sustainable irrigated agriculture in Mediterranean island communities – Insights from Malta. (June 2019) - Papadimitriou, Lamprini; D'Agostino, Daniela; Borg, Malcolm; Hallett, Stephen; Sakrabani, Ruben; Thompson, Andrew; Knox, Jerry
The future sustainability of irrigated agriculture in Mediterranean island communities faces a raft of economic, environmental and socio-economic challenges. Many of these are inextricably linked to the extreme levels of water scarcity that exist in the region. With a focus on Malta, we developed a water strategy to identify the priorities for action to support decision makers, practitioners and the agrifood industry in achieving agricultural and water resources sustainability. The methodology involved a combination of evidence synthesis, to inform the development of a Drivers-Pressures-State-Impact-Response framework. These priorities were then used to define a set of key actions under three thematic pillars of sustainability (environment, economy and society). Our analysis confirmed that irrigated agriculture in Malta is not only impacted by environmental factors such as the challenging climate and geography of the region but also strongly influenced by a range of economic (tourism development, European Union accession) and societal (population growth, environmental regulation) drivers of change. The developed strategy is underpinned by priority actions relating to improved water and soil management. The reduction of water and energy footprints in crop production, the establishment of demonstration farms and the support of policies that promote 'value adding' activities are examples of key priority actions for the environmental, economic and societal pillar, respectively. Regarding the scale of intervention, the analysis distinguishes research as being important for supporting many of the economy-focused actions.